Correlations between radio and bolometric fluxes in GX 339–4 and H1743–322. Issue 4 (5th October 2018) - Islam, Nazma; Zdziarski, Andrzej A
Abstract: Compact radio jets are ubiquitous in stellar-mass black hole binaries in their hard spectral state. Empirical relations between the radio and narrow-band X-ray fluxes have been used to understand the connection between their accretion discs and jets. However, a narrow-band (e.g. 1–10 or 3–9 keV) X-ray flux can be a poor proxy for either the bolometric luminosity or the mass accretion rate. Here, we study correlations between the radio and unabsorbed broad-band X-ray fluxes, the latter providing good estimates of the bolometric flux. We consider GX 339–4, the benchmark object for the main branch of the correlation, and H1743–322, the first source found to be an outlier of the correlation. The obtained power-law dependences of the radio flux on the bolometric flux have significantly different indices from those found for the narrow X-ray bands. Also, the radio/bolometric flux correlations for the rise of the outbursts are found to be significantly different from those for the outburst decline. This points to a possible existence of a jet hysteresis in the radio/X-ray source evolution, in addition to that seen in the hardness/flux diagram of low-mass X-ray binaries. The correlation during the rise of the outbursts is similar for both GX 339–4 and H1743–322. The correlation for the decline of the outbursts for H1743–322 lies below that of GX 339–4 at intermediate X-ray fluxes, whereas it approaches the standard correlation at lower X-ray luminosities. We also compare these correlations to those for the high-mass X-ray binaries Cyg X-1 and Cyg X-3.